Pola Pemilihan Asimetris dalam Pemilihan Umum sebagai Solusi Transisi Demokrasi di Masa Pandemi - Sun Fatayati; Ahmad Gelora Mahardika (Institut Agama Islam Tribakti (IAIT) Kediri, 2022)
The covid-19 pandemic outbreak that has occurred in Indonesia since March 2020 has forced the Government to postpone the simultaneous Regional Head Election which is planned to be held in September 2020. The problem is that the norms governing the implementation of Pilkada in September are written concretely in Law Number 10 of Year In 2016, the implication is that the government only has two options related to simultaneous regional elections in the middle of a pandemic, namely to postpone or continue implementing it with the risk of voters being infected with an outbreak. The government finally decided to postpone through Government Regulation in lieu of Law Number 2 of 2020 which in one article stated that the implementation of the Pilkada was carried out in December 2020. However, these changes were only temporary and had high risks, this was due to concerns. related to the implementation of elections in the midst of an outbreak and there are concerns if the outbreak occurs in the national election. Therefore, the change in the selection method with the asymmetrical selection model is the right alternative solution to be applied in the midst of a pandemic outbreak. The research method in this article is normative juridical. The conclusion in this study is that changes in the method of selection can be made and it is not against the law.